Pengaruh Disiplin Dan Kemampuan Kerja Terhadap Kinerja Pegawai di Badan Pengelolaan Keuangan dan Aset Daerah Provinsi Sumatera Selatan - Triani, Evon; Sakir, Icuk Muhammad; Novaria, Eva (@-Publik: Jurnal Administrasi Publik, 2026)
As a component of public administration, civil servants can realize the vision and mission that have been set by carrying out their duties well, and professional civil servants are expected to play a role in assisting public administrators in carrying out their duties. . The performance report of regional office employees of the South Sumatra Province Financial and Asset Management Agency did not show good results. This is believed to still be caused by poor working conditions and work discipline. Job responsibilities are very important. When employees are responsible for their work, they will use all their abilities to achieve satisfactory work results. The results of the hypothesis test on the influence of work order variables on employee productivity obtained a calculated t value = 0.315 > t table = 1.664, a significance index of 0.753. This proves the hypothesis that work discipline has a positive effect on employee productivity. For the employment variable, the regression coefficient or β1 = 0.036 means that the greater the employment, the higher the employee productivity. Employee performance has a very close relationship to employee discipline and work ability, this can be seen from the value <a = 0.05 so it is significant.